Tall building: effect of variation of spandrel beams on capacity of lateral resistance in a coupled-shear-wall - Liew, Brenda Wan Wen (2014)
Shear walls are commonly used in tall building to resist lateral loadings. However, due to design constrains such as windows, stairs and doorway, there will be openings in these shear walls. These types of walls are also known as coupled shear wall. Many studies have been carried out to study the effect of varying various parameters of the beam under static and seismic loadings. However, little research has been done to investigate the behaviour of the coupled shear wall as a system. This project focuses on investigating the effect of variation of spandrel beam on the shear forces at the ends of the beam in a coupled shear wall system. Analysis was done using finite element method by the software SAP 2000. A 20 storey tall stimulation of a shear wall will be subjected to static and dynamic loadings and the shear force of the spandrel beams and deflection of the coupled shear wall are studied. The analysis concluded that shear force is dependent on the span depth ratio of the spandrel beam. Also, deflection under different loading will produce different trends due to the SDR.